Right-wing populism and market-fundamentalism: Two mutually reinforcing threats to democracy in the 21st century - Walter Ötsch; Stephan Pühringer (Cusanus Hochschule, Institut für Ökonomie und Institut für Philosophie, 2017)
The article compares market fundamentalism and right-wing populism on the basis of its core patterns of thinking and reasoning. Based on an analysis of important texts in both fields we find many similarities of these two concepts in their "inner images". Thus, we develop a scheme of the similar dual social worlds of right-wing-populism and market fundamentalism and offer some recent examples of market fundamentalism and right-wing populism mutually reinforcing each other or serving as a gateway for each other. We then apply our scheme for the analysis of the recent political developments and its ideological roots in the US under Donald Trump.
Keywords: A12; A14; B25; P16; N42; N44; P16; 330; Right-wing populism; market-fundamentalism; inner images; Donald Trump; patterns of thinking